Determinants of portfolio flows into CIS countries - Oleksandr Lozovyi; Alina Kudina (Center for Social and Economic Research (CASE), 2007)
This paper employs a standard Tobin-Markowitz framework to analyse the determinants of capital flows into the CIS countries. Using data from 1996-2006, we find that the Russian financial crisis of 1998 has had a profound impact on capital flows into the CIS (both directly and indirectly). Firstly, it introduced a structural shift in the investors' behaviour by shifting the focus from the external factors to the internal ones, e.g. domestic interest and GDP growth rates. Secondly, it also drastically changed the impact of a number of explanatory variables on capital flows into the CIS. Political risk was found to be the second most important determinant of capital flows into the CIS. Additionally, we report some strong evidence of co-movement between portfolio flows into the CIS and CEEC, coupled with strong complementarity between global stock market activity and portfolio inflows into the CIS. Interestingly, external factors tend to be of a higher significance than internal factors for the largest members (Russia, Ukraine and Kazakhstan) of the CIS; whereas domestic variables tend to have a greater impact on the capital flows into the smaller CIS countries.
Keywords: E44; F3; F32; 330; portfolio investment; CIS; the Russian crisis; emerging markets; Portfolio-Investition; GUS-Staaten; Finanzkrise; Russland